Order Allocation Model Considering Transportation Alternatives and Lateral Transhipment - Ashylla Maharani; Cucuk Nur Rosyidi; Pringgo Widyo Laksono (Jurnal Optimasi Sistem Industri, 2022)
Intense competition among companies encourages them to provide the best quality of products in competitive price. It is important for company to manage supply chain properly in order to achieve that. Selecting the best reliable supplier is the key to reduce purchasing cost, increase customer satisfaction and improve the competitive ability. In this study, we develop an order allocation model in multi echelon environment which includes supplier, manufacturer, and retailer. We consider transportation alternatives for the shipment from supplier to manufacturer and also the shipment from manufacturer to retailer. This model allows lateral transshipment between retailers. A Mixed Integer Linear Programming (MILP) is used to model the system. Sensitivity analysis is conducted at the end of the research. The result shows that the retailer demand, lead time, material variable price are sensitive to the objective function while the transportation costs from supplier to manufacturer, from manufacturer to retailers, and between retailers are not sensitive to the objective function. Retailer demand parameter is also sensitive to all decision variables. The transportation cost from supplier to manufacturer, material prices, and lead time are sensitive to the order allocation from manufacturer to supplier, while transportation cost from manufacturer to retailers and transportation cost between retailers are sensitive to the allocation of product sent from the manufacturer to retailers and the allocation of product sent between retailers.